Communication during Disaster Recovery - World Bank (World Bank, Washington, DC, 2020)
This guide provides practical guidance for governments regarding how to effectively communicate with communities during the recovery phase following an emergency. It explains how to identify communication needs and presents best fit communication methods and strategies to deploy to support disaster recovery frameworks (DRF) and recovery strategies. For the purposes of this guide, recovery communication includes sending, gathering, managing, and evaluating information. Communication flows between governments and communities can be one-way, whereby information is sent out to communities, and or two-way, whereby communities have an opportunity to voice their views and opinions to governments. This guide focuses on external government communication with individuals and communities.